2013
DOI: 10.1021/ja4017683
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur(IV)-Mediated Transformations: From Ylide Transfer to Metal-Free Arylation of Carbonyl Compounds

Abstract: The development of a direct ylide transfer to carbonyl derivatives and of a sulfoxide-mediated arylation is presented from a unified perspective. Mechanistic studies (including density functional calculations) support a common reaction pathway and showcase how subtle changes in reactant properties can lead to disparate and seemingly unrelated reaction outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(41 citation statements)
references
References 106 publications
1
37
0
3
Order By: Relevance
“…Recently, we34353637383940 and others41424344454647484950515253545556 reported the metal-free, sulfoxide directed57 C–H functionalization of a variety of molecular scaffolds, which was enabled by an interrupted Pummerer reaction28. Spurred on by these recent achievements, we considered the use of benzothiophene S -oxides 1 for the synthesis of important C3-functionalized benzothiophenes, as the corresponding sulfonium salts I and II , formed after reaction with the coupling partners, lack aromaticity about the five-membered ring and should therefore undergo facile C–C bond formation via [3,3]-sigmatropic rearrangement58, thus delivering unexplored reactivity not accessible in benzothiophenes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we34353637383940 and others41424344454647484950515253545556 reported the metal-free, sulfoxide directed57 C–H functionalization of a variety of molecular scaffolds, which was enabled by an interrupted Pummerer reaction28. Spurred on by these recent achievements, we considered the use of benzothiophene S -oxides 1 for the synthesis of important C3-functionalized benzothiophenes, as the corresponding sulfonium salts I and II , formed after reaction with the coupling partners, lack aromaticity about the five-membered ring and should therefore undergo facile C–C bond formation via [3,3]-sigmatropic rearrangement58, thus delivering unexplored reactivity not accessible in benzothiophenes.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al [90] reported the TMF carbon arylation from carbonyl compounds via ylide with sulphur-mediated transformations (Scheme 45). Interestingly, the above protocol leads to irrelevant sulphur biaryl 129 outcomes.…”
Section: Miscellaneous Arylationmentioning
confidence: 99%
“…4, entries 8–11) because cyclohexanone is structurally more rigid than either cycloheptanone and acyclic aliphatic ketones, which makes cyclohexanone less reactive towards the C−C bond formation414243. The three-component reaction mentioned above provides a convenient access to α-aryl ketones4142444546474849 having a trifluoromethyl group on the aryl ring (Fig. 1)2427 in a single operation505152535455.…”
Section: Resultsmentioning
confidence: 99%